Vegetation and seed bank of an open-scrub bush restinga formation in the southeastern coast of Brazil - Bechara, Fernando Campanhã (2018)
Restingas are coastal plain ecosystems located along Eastern Brazil, corresponding to about 5 000 km. The restinga vegetation is associated with the Atlantic rainforest biome and comprises four distinct main formation zones: coastal grasslands, shrublands, open-forests and marsh zones. Especially due to coastal urbanization, this is a threatened ecosystem that, through its different shrub formations, exhibits a unique mosaic as a result of the vegetation distribution in nuclei of different covering, physiognomy and floristic composition. Objective: We aimed to characterize the above and belowground composition of a conserved, non-flooded, open-scrub, nuclei (patches of bushes) formation of restinga in Linhares, ES, southeastern Brazil. Methods: The vegetation survey was conducted using the line intercept method. Diameter and height of the first six nuclei were measured in five transects separated by 50 m, totaling 30 nuclei up to 350 m away from the shore line. The phytosociology and Shannon Index of the aboveground vegetation community were calculated. In the same 30 nuclei, leaf litter and topsoil layer (15 x 15 x 10 cm) samples were collected to survey the viable seed bank, which was later placed in a greenhouse for germination and seedling identification. The Sørensen Similarity index (SSi) was used to compare the floristic composition between the leaf litter and topsoil layer seed banks. Nuclei volume and number of species were calculated as well. Results: In the aboveground vegetation, 54 plant species belonging to 32 families were identified, totaling 1 098 individuals. The nuclei showed a diversity (H’) of 3.08 nats, and an average diameter of 11.5 m (s = 9.1), area of 526.4 m2 (s = 1 081.7), and height of 2.9 m (s = 1.1). Davilla flexuosa, followed by Smilax rufescens, presented the highest IVI (Importance Value Index). A total of 1 839 seedlings from 32 species and 19 families were identified in the seed bank. Enydra sessilis (Asteraceae) had the highest seed density (544), while the family with highest species richness was Cyperaceae. A low similarity between the vegetation surveyed and the seed bank composition was found (only 5 species in common, SSi = 0.10). Conclusions: The results indicate that a post-disturbance early community, established from the seed bank, would have a substantially different species composition, but with other potential species to restore vegetation over the long-term succession.